Analysis of the Influence of Organizational Culture, Work Motivation, and Work Discipline on Employee Productivity at The Cianjur Pratama Tax Service Office - Taufik Sholeh; Kuswandi; Sri Rahayu; Rifda Fitrianty (International Publisher, 2025)
An agency is required to have human resources that have work motivation, organizational culture, and a disciplined attitude to increase the work productivity of an employee, work discipline is the most important human resource management function and is closely related to resource management for an organization. Therefore, this study aims to examine the influence between organizational culture, work motivation, and work discipline on employee productivity at work. The sample in this study were 96 employees at the Cianjur Primary Tax Service Office. The analytical tool used is multiple linear regression. The results showed that partially the variables of organizational culture and work motivation had a significant effect on employee work productivity, but partially the work discipline variable had no effect on employee work productivity. Then simultaneously the variables of organizational culture, work motivation, and work discipline affect the work productivity of employees at the Cianjur Primary Tax Service Office.